Evaluating the validity of depression-related stigma measurement among diabetes and hypertension patients receiving depression care in Malawi: A mixed-methods analysis. - Josée M Dussault; Christopher Akiba; Chifundo Zimba; Jullita Malava; Harriet Akello; Melissa Stockton; MacDonald Mbota; Maureen Matewere; Jones Masiye; Michael Udedi; Bradley N Gaynes; Vivian F Go; et al. (Public Library of Science (PLoS), 2023)
Mental illness stigma research is sparse in Malawi. Our team previously analyzed the reliability and statistical validity of a quantitative tool to measure depression-related stigma among participants with depressive symptoms using quantitative psychometric methods. This analysis aims to further evaluate the content validity of the stigma tool by comparing participants' quantitative responses with qualitative data. The SHARP project conducted depression screening and treatment at 10 noncommunicable disease clinics across Malawi from April 2019 through December 2021. Eligible participants were 18-65 years with depressive symptoms indicated by a PHQ-9 score ≥5. Questionnaires at each study timepoint included a vignette-based quantitative stigma instrument with three thematic domains: disclosure carryover (i.e., concerns about disclosure), treatment carryover (i.e., concerns about external stigma because of receiving depression treatment), and negative affect (i.e., negative attitudes about people having depression). Sub-scores were aggregated for each domain, with higher scores indicating greater stigma. To better understand participants' interpretation of this quantitative stigma questionnaire, we asked a subset of six participants a parallel set of questions in semi-structured qualitative interviews in a method similar to cognitive interviewing. Qualitative responses were linked with participants' most recent quantitative follow-up interviews using Stata 16 and NVivo software. Participants with lower quantitative stigma disclosure sub-scores had qualitative responses that indicated less stigma around disclosure, while participants with higher quantitative stigma sub-scores had qualitative responses indicating greater stigma. Similarly, in the negative affect and treatment carryover domains, participants had parallel quantitative and qualitative responses. Further, participants identified with the vignette character in their qualitative interviews, and participants spoke about the character's projected feelings and experiences based on their own lived experiences. The stigma tool was interpreted appropriately by participants, providing strong evidence for the content validity of the quantitative tool to measure these stigma domains.